Kebijakan Pengembangan Terbitan Berkala di Perpustakaan Fakultas Ilmu Budaya Universitas Andalas - Sasmita, Erni; Primadesi, Yona (Ilmu Informasi Perpustakaan dan Kearsipan, 2014)
Collection development policy paper periodicals in the Library of the Faculty of Humanities, University of Andalas which discusses the applicability and constraints as seen from the collection development process starting from the requirements analysis process, the selection policy, selection, procurement, weeding and evaluation. This study is a qualitative study using descriptive research method. Data collection techniques used in this study is observation and interviews. Informants in this study is an expert associate librarian at the Library of the Faculty of Humanities. The results of this study showed that the Faculty of Cultural Sciences Library does not yet have a collection development policy periodicals written. This led to the development of the collection can be summed up by a bad run. Collection development process is also carried out without regard to the needs of library users. Keywords: collection development policy; periodicals